Moderating effect of personal characteristics on telecentre adoption for value creation in Malaysia - Md Dahalin, Zulkhairi; Yusop, Nor Iadah; Mat Aji, Zahurin (2016)
This paper examines the influence of personal characteristics of community within the vicinity of rural telecentres on the relationship between adoption of ICT and value creation. The aim was to identify characteristics of members of the community that have positive or negative influence on the adoption of the telecentre in order to gain socio-economic impact.A survey was conducted among the community within the vicinity of the telecentres where data was gathered on respondents’ demography, their perceptions on availability of ICT facilities at the telecentre, and the benefits gained from using the ICT facilities.The Diffusion of Innovation theory was used to guide the research and moderating analysis was used as data analysis. Results show that age, gender, marital status and PC ownership as significant moderators that affect the relationship between telecentre adoption and value creation.